¿Qué esconde la imagen de una unión idealizada? Beatriz Ñusta y la caída del Imperio inca en cuatro cuadros coloniales - Artzi, Bat-ami (Pontificia Universidad Católica del Perú, 2024)
This article analyzes four colonial paintings from the Viceroyalty of Peru that depict the union of Beatriz Ñusta and Martín de Loyola, as well as the marriage of their daughter. From a feminist perspective, it explores the pictorial and historical representations of Beatriz Ñusta and the possible connections between them. The iconographic analysis presented in this article highlights the agency of the Indigenous or mestizo artists who created these paintings. Furthermore, the study of the iconographic differences found in these paintings, as well as a metal plaque that represents part of the scene, reveals variations related to the audiences for which these artworks were intended.

Este artículo analiza cuatro cuadros coloniales del Virreinato del Perú que representan la unión de Beatriz Ñusta y Martín de Loyola, así como el matrimonio de su hija. Desde una perspectiva feminista, explora la representación pictórica e histórica de Beatriz Ñusta y la posible conexión entre ambas. El análisis iconográfico presentado aquí evidencia la agencia de los o las artistas de origen indígena o mestizo que crearon estas pinturas. Asimismo, el estudio de las diferencias iconográficas encontradas en estos cuadros y en una placa de metal que representa parte de la escena revela variaciones en torno a los públicos a los que estaban destinadas estas obras.
What does the image of an idealized union conceal? Beatriz Ñusta and the fall of the Inca Empire in four colonial paintings
Keywords: Beatriz Ñusta; Marriage; Imposition; Agency; Beatriz Ñusta; Matrimonio; Imposición; Agencia; https://purl.org/pe-repo/ocde/ford#6.01.01